THE ROLE OF THE MINISTRY OF RELIGION IN PROMOTING RELIGIOUS MODERATION IN THE DIGITAL ERA - A, Sulastri; Fitri, Humaira Nurwani; Zafira, Nurul; Syari, Sabila Rahma; Prawardani, Diah Arum (Proceeding International Seminar of Islamic Studies, 2024)
Religious moderation is an important key in minimizing radical acts and extremism in religion in Indonesia. The Ministry of Religion is an important element in being responsible for religious harmony in Indonesia. The program to strengthen religious moderation was also intensified in 2019 by the Ministry of Religion. The author uses a qualitative research approach for this research method. Based on the results of research conducted by researchers, it is